Identification of The First Limiting Amino Acid In Cooked Polished White Rice Fed To Weanling Holtzman Rats - Masrizal, Mellova; Lamb, J. B. (Makara Journal of Technology, 2003)
Forty-eight male weanling rats (91 g) were utilized to study the nutritional adequacy of cooked polished white rice. Rats were individually housed, and allowed ad libitum access to one of six treatment diets. Treatment diets were 1) polished white rice plus 10% casein and 0.18% methionine, CAS, 2) polished white rice, WHR, 3) polished white rice plus 0.45% lysine, LYS, 4) polished white rice plus0.40% methionine, MET, 5) polished white rice plus 0.30% threonine, THR, 6) polished white rice plus 0.45% lysine, 0.40% methionine, and 0.40% threonine, COM. Rice was cooked prior diet formulation using a 3 to 1 ratio of water to rice. Vitamins (AIN-76) and AIN minerals were added to all diets to meet NRC (1978) requirements. Rats fed CAS diets were significantly heavier on d 21 (P0.05) rat performance over WHR fed rats, Average daily gain (ADG) for CAS was 6.1 g/d and ADG for LYS and MET was 3.0 g/d. The addition of threonine (THR) significantly (P